Caring For Performance: Recent Debates - Hanna B. Hölling (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Can performance art be conserved? If so, how, and if not, why not? Enhanced by short philosophical reflection surrounding conservation and its entanglement with the world, this essay reviews the debates that took place on the occasion of the international colloquium devoted to the conservation of performance, Performance: The Ethics and the Politics of Care. The colloquium was organized at Bern University of the Arts on May 29-30, 2021 within the research project Performance: Conservation, Materiality, Knowledge (Swiss National Science Foundation, 2020-24). The essay investigates the notion of performance through the lens of its conserveability and through a multidisciplinary perspective represented by a diversity of voices during the colloquium. It ultimately presents both performance and conservation as inherently unstable categories that require a careful and reflective approach.